Acute Surgical and Rehabilitation Management of Complex Hand Burns in Combat Casualties - Jill M. Cancio; Jonathan B. Lundy; Leopoldo C. Cancio (MDPI AG, 2024)
Burns are inevitable in modern warfare and have comprised between 5% and 20% of battlefield injuries. Involvement of the hands is the leading cause of postburn functional impairment. The purpose of this paper is to provide guidance on aspects of care necessary for the management of complex hand burns in a battlefield setting. Proper assessment and establishment of a comprehensive plan of care at the onset of injury help to ensure optimal functional outcomes in hand function. Basic treatment principles for the acutely burned hand include edema management; early wound coverage, including excision of the burn and skin grafting; early and aggressive hand therapy; and burn-scar contracture mitigation strategies.